Design, Manufacture and Evaluation of Oat De-Husking Machine - Kaumars Merikhi; Hekmat Rabbani; sohbat Bahraminejad (Biomechanism and Bioenergy Research)
Peeling is an essential step in oat processing. In the operation of peeling oats with peeling machines, a percentage of oats will break and cause quality waste in the product. In this study for the first time, the skin-separating mechanism was created by the contact of two surfaces of the conveyor belt, where the belt passes by the seeds at a higher speed. The upper and lower belts are flat types with 2 mm space, based on the average value of the width of six varieties of oats. The lower belt has a lower speed than the upper belt, the seeds fall on it and move forward. While the upper belt has a higher speed, it causes the rotational movement of the seed by moving on the seeds, and while the seed is between the two belts, it is under pressure, and due to this pressure and rotational movement, the seed skin is broken and separated. To prevent the lower belt from bending, a tray is installed under the lower belt. The amount of dehulled grain is calculated based on the speed of the lower belt. According to the calculations, having a reliability factor of 2, an electric motor of 4 horsepower at 1500 rpm has been selected. The upper speed of the belt is 31.4 m/min and the outlet opening of the tank is 0.003 m2. The amount of peeled oats is 486 kg per hour. In the evaluation of the peeling machine, 76% of Euro varieties was obtained.